PENINGKATAN SELF-EFFICACY DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN GUIDED INQUIRY PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) - Ilham Hadi; Sutarto; Sabrun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students’ self-efficacy and mathematical problem-solving skills through the implementation of the Guided Inquiry learning model on the topic of Systems of Linear Equations in Two Variables (SLETV). The study employed a Classroom Action Research (CAR) design conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 26 eighth-grade students of MTs NW Embung Raja in the 2025/2026 academic year. Data were collected through observation, self-efficacy questionnaires, mathematical problem-solving tests, and documentation. The findings revealed that the implementation of the Guided Inquiry model improved all observed aspects. Student activity increased from 52.38% in Cycle I to 87.62% in Cycle II, while teacher activity increased from 48.81% to 78%. Students’ self-efficacy improved from 65.58% (high category) to 97.84% (very high category). Mathematical problem-solving skills also improved, as indicated by the increase in the average score from 63.58 in Cycle I to 85.38 in Cycle II. The number of students achieving the minimum mastery criterion increased from 6 students to 22 students. These results indicate that the Guided Inquiry learning model is effective in improving students’ self-efficacy and mathematical problem-solving skills in learning systems of linear equations in two variables.